Research and Development in Work and Technology
XIV, 413 p. 13 illus.
Keywords: European Problem Areas of Coordinating Research and Development Strategies in Work and Technology Introduction Hans Pomschlegel, Dortmund, Germany 1. Initiative and Organizers During several meetings in Stockholm between the Swedish-German steering group of the Swedish Work Environment Fund (Arbetsmiljofonden) and the Project Ad ministration for Work and Technology (Projekttrager Arbeit und Technik) of the DLR it was common opinion that the coordination of some programme areas and projects of both sides, and the cooperation within them, showed good progress and fruitful results. Contacts and cooperation between research institutions and researchers were also well underway. But there was never time to discuss political, strategic and operational approaches in the formulation, interpretation and implementation of research and development (R&D) strategies in the common fields of activities, labelled "quality of working life", "humanization", anthropocentric design concepts, work and technology, to mention the most common terms in English. Last year the Sozialakademie Dortmund proposed to the Swedish and German parties to organize a workshop devoted to this cause. The idea was immediately taken up; the German side suggested that such a gathering should not only express German and Swedish voices but should be extended to a wider, European forum. The workshop could then better deal with the relations between the relevant national, European and possibly international programmes. It would allow deeper insights into the underlying political structures and mechanisms, the system of cooperation and conflict solving between publicly financed programmes, promoted institutions and expected results.